Impact of the 2017 American Heart Association and American College of Cardiology hypertension guideline in aged individuals. Issue 12 (December 2020) - Chowdhury, Enayet Karim; Ernst, Michael E.; Nelson, Mark; Margolis, Karen; Beilin, Lawrie J.; Johnston, Collin; Woods, Robyn; Murray, Anne; Wolfe, Rory; Storey, Elsdon; Shah, Raj C.; Lockery, Jessica; et al.
Abstract : Objectives: The AHA/ACC-2017 hypertension guideline recommends an age-independent target blood pressure (BP) of less than 130/80 mmHg. In an elderly cohort without established cardiovascular disease (CVD) at baseline, we determined the impact of this guideline on the prevalence of hypertension and associated CVD risk. Methods: Nineteen thousand, one hundred and fourteen participants aged at least 65 years from the ASPirin in Reducing Events in the Elderly (ASPREE) study were grouped by baseline BP: 'pre-2017 hypertensive' (BP ≥140/90 mmHg and/or on antihypertensive drugs); 'reclassified hypertensive' (normotensive by pre-2017 guidelines; hypertensive by AHA/ACC-2017 guideline), and 'normotensive' (BP <130 and <80 mmHg). For each group, we evaluated CVD risk factors, predicted 10-year CVD risk using the Atherosclerotic Cardiovascular Disease (ASCVD) risk equation, and reported observed CVD event rates during a median 4.7–year follow-up. Results: :Overall, 74.4% (14 213/19 114) were 'pre-2017 hypertensive'; an additional 12.3% (2354/19 114) were 'reclassified hypertensive' by the AHA/ACC-2017 guideline. Of those 'reclassified hypertensive', the majority (94.5%) met criteria for antihypertensive treatment although 29% had no other traditional CVD risk factors other than age. Further, a relatively lower mean 10-year predicted CVD risk (18% versus 26%, P < 0.001) and lower CVD rates (8.9 versus 12.1/1000 person-years, P = 0.01) were observed in 'reclassified hypertensive' compared with 'pre-2017 hypertensive'. Compared with 'normotensive', a hazard ratio (95% confidence interval) for CVD events of 1.60 (1.26–2.02) for 'pre-2017 hypertensive' and 1.26 (0.93–1.71) for 'reclassified hypertensive' was observed. Conclusion: Applying current CVD risk calculators in the elderly 'reclassified hypertensive', as a result of shifting the BP threshold lower, increases eligibility for antihypertensive treatment but documented CVD rates remain lower than hypertensive patients defined by pre2017 BP thresholds. Abstract : Supplemental Digital Content is available in the text